2018
DOI: 10.1167/iovs.17-23282
|View full text |Cite
|
Sign up to set email alerts
|

BMP and Activin Membrane Bound Inhibitor Regulates the Extracellular Matrix in the Trabecular Meshwork

Abstract: PurposeThe trabecular meshwork (TM) has an important role in the regulation of aqueous humor outflow and IOP. Regulation of the extracellular matrix (ECM) by TGFβ2 has been studied extensively. Bone morphogenetic protein (BMP) and activin membrane-bound inhibitor (BAMBI) has been shown to inhibit or modulate TGFβ2 signaling. We investigate the role of TGFβ2 and BAMBI in the regulation of TM ECM and ocular hypertension.MethodsMouse TM (MTM) cells were isolated from B6;129S1-Bambitm1Jian/J flox mice, characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 72 publications
(118 reference statements)
2
27
0
Order By: Relevance
“…BAMBI was a TGF-β pseudoreceptor ,and down-regulation of BAMBI made HSCs beccome more sensitive to TGF-β [18], that was the main mechanism of endotoxin-induced hepatic brosis [19,20]. HSCs was the naïve cells that responds to LPS by TLR4 [21], BAMBI was down-regulated after TLR4-MyD88-NF-κB pathway was activated in HSCs [22].…”
Section: Discussionmentioning
confidence: 99%
“…BAMBI was a TGF-β pseudoreceptor ,and down-regulation of BAMBI made HSCs beccome more sensitive to TGF-β [18], that was the main mechanism of endotoxin-induced hepatic brosis [19,20]. HSCs was the naïve cells that responds to LPS by TLR4 [21], BAMBI was down-regulated after TLR4-MyD88-NF-κB pathway was activated in HSCs [22].…”
Section: Discussionmentioning
confidence: 99%
“…Ad5.Null virus (Vector Biolabs, Malvern, PA, USA) was used as a negative control. Briefly, 2 μL of 2.5 × 10 7 plaque-forming units (pfu) was intravitreally injected into one eye, and the uninjected contralateral eyes were used as negative controls as previously described 13,15 . intraocular pressure Measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the ECM composition of the TM is important in regulating aqueous humor outflow and forming a fluid flow pathway for proper aqueous humor drainage 9,10 . It is also known that POAG patients have an increased accumulation of ECM proteins within the TM 11,12 , increased ECM production leads to an increase in aqueous humor (AH) outflow resistance 13 , decreases AH outflow facility [14][15][16][17][18] , and causes ocular hypertension 13,15,19,20 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Associations between refractive error and genes involved in ECM growth and remodeling have been reported in individual gene studies, and in genome-wide association studies (25,26,58–64). In the eye, BMPs have been shown to inhibit excessive TGF-β2 induction of ECM proteins (6569). Since we have shown that absence of Lrp2 leads to modulation of genes influenced by Bmp overexpression, we hypothesized that Lrp2 may assist in fine-tuning Bmp levels to properly control deposition and turnover of ECM proteins.…”
Section: Resultsmentioning
confidence: 99%